Pengaruh Arus Kas Operasi Dan Laba Akuntansi Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Ni Nyoman Trisia; Olviane. O. Sumampouw (Fakultas Ekonomi Universitas Negeri Manado, 2022)
This study aims to find out the effect of Operating Cash Flow and Accounting Profit with Stock Returns in Manufacturing Company in the Consumer Goods Industry Sector that Listed at the Indonesia Stock Exchange for the Period 2017-2019. The type of research used in research is quantitative. The type of data used is secondary data obtained from the company's annual financial statements through the official website of the Indonesia stock exchange www.idx.co.id. In determining the sample using purposive sampling techniques, so the study sample was 30 companies with a 3-year observation period that is 2017-2019, so that the total number of observations is 90. The data analysis technique used when testing hypotheses is Multiple Linear Regression Analysis. The results showed that Operating Cash Flow had no effect on stock returns and accounting earnings had no effect on stock returns.